2015
DOI: 10.1002/2015jc010703
|View full text |Cite
|
Sign up to set email alerts
|

Ocean variability east of Mindanao: Mooring observations at 7°N, revisited

Abstract: Two subsurface moorings were deployed east of Mindanao Island, the Philippines, at 7°01′N, 126°55′E and 7°01′N, 127°46′E, at the location of the inshore and offshore cores of the Mindanao Undercurrent (MUC) suggested by past studies, from September 2011 to October 2012 and March 2013. A steady northward undercurrent, the MUC, was not confirmed by these observations, not only at the location of its inshore core but also of the offshore core. The observed mean flow at the mooring sites seems to be part of an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The complicated and chaotic structures near the western boundary in Figure indicate that mesoscale eddies may also have significant influence on the seasonal variability of the MUC. In January and July, the enhanced MUC is likely the inshore component of an anomalous anticyclonic gyre residing east of Mindanao, which is in line with several existing studies (Firing et al, ; Kashino et al, ; Qu et al, ; Wang et al, ). This also likely explains why neither the winter MUC nor the summer MUC flows in the direction of the coast geometry in mooring observation (Figure ).…”
Section: Dynamics Of the Seasonal Variabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…The complicated and chaotic structures near the western boundary in Figure indicate that mesoscale eddies may also have significant influence on the seasonal variability of the MUC. In January and July, the enhanced MUC is likely the inshore component of an anomalous anticyclonic gyre residing east of Mindanao, which is in line with several existing studies (Firing et al, ; Kashino et al, ; Qu et al, ; Wang et al, ). This also likely explains why neither the winter MUC nor the summer MUC flows in the direction of the coast geometry in mooring observation (Figure ).…”
Section: Dynamics Of the Seasonal Variabilitysupporting
confidence: 89%
“…However, the MUC was not observed by some observations (Kashino et al, ; Wijffels et al, ). Kashino et al () deployed two moorings at 7°N and obtained current records of the upper 350 m and at depths of 560, 960 and 1,460 m, but they did not observe steady northward flow structure resembling the MUC. Recent studies suggested that the mean current below the thermocline is northward but subjected to strong variability (Hu et al, ; Qiu et al, ; Schönau & Rudnick, ; Wang et al, ; Zhang et al, ), such as the strikingly prominent intraseasonal variability of 50–100 day periods revealed by mooring observation (Kashino et al, ; Zhang et al, ) and model simulations (Qu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The ME, defined as a persistent eddy that feeds into the MC, is sometimes difficult to see in synoptic hydrographic sections (Wijffels et al, 1995;Kashino et al, 2013), yet it frequently appears as a mean feature and has been resolved using surface drifters (Lukas et al, 1991). The MUC, typically located within 200 km of the shore, has been studied using mooring and modeling efforts to determine whether it is a persistent northward flow (Qu et al, 2012;Zhang et al, 2014) or part of a variable anticyclonic eddy (Kashino et al, 2015). Due to the variability of the ME and the MUC, identifying these features and understanding their relationship to the regional circulation is an ongoing area of research.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…The characteristics of the NP brought by MC are dissimilar to those from SP brought by NGCC/NGCUC. MC is a part of LLWBC in NP, formed when NEC impairs Philippine's eastern coast (Kashino et al, 1996;Kashino et al, 2013;Kashino et al, 2015). MC transports NP's water mass and mixes them when flowing to the south from the Philippine Sea, supplying the tropical circulation in the North Pacific and Indian Oceans (via ITF).…”
Section: Discussionmentioning
confidence: 99%